Circulation and containment in the knowledge-based economy: Transnational education zones in Dubai and Qatar - Tim Rottleb; Jana M. Kleibert (Environment and Planning A: Economy and Space, 2022)
Our analysis focuses on evolving global capitalism's production of high-skilled temporary migrant labour through the technology of special economic zones. Drawing on debates in economic geography on zones as globalised spaces of production and interdisciplinary scholarship on economic transformation in the Arabian Peninsula, we interrogate a relatively new type of zone that agglomerates foreign higher education institutions: transnational education zones. We conceptualise these zones as a distinct form of exceptional space produced by aspirations for a knowledge-based economy. Transnational education zones provide financial benefits and legal exemptions to state territory for international higher education investors who operate offshore campuses. By conducting a situated empirical analysis of transnational education zones' logics and mechanisms in Dubai and Qatar, we show how these zones function as sites of circulation and containment that allow governments to harness globally circulating people and institutions for building a knowledge-based economy, while aiming to contain their social and political impact locally. While the underlying contradictions of simultaneous circulation and containment of knowledge and knowledge workers are modulated by the exceptional character of the zones, they cannot be fully resolved. In many ways, transnational education zones constitute a continuation of established strategies for economic development by exception that have been pursued by governments in the Gulf, which aim for global connectivity and rely heavily on controlling a temporary and contingent migrant workforce.
Keywords: 710; Special economic zones; circulation and containment; knowledge-based economy; transnational education; Arab Gulf